Răspuns :
[tex]2^{2n+1}\cdot 3^{n}+4^{n}\cdot3^{n+2}=\\ \\=2^{2n}\cdot 2\cdot 3^{n}+4^{n}\cdot 3^{n}\cdot 3^{2}=\\ \\ =(2^{2})^{n}\cdot 3^{n} \cdot 2 +4^{n}\cdot 3^{n}\cdot 9=\\ \\ =4^{n}\cdot 3^{n}\cdot 2+4^{n}\cdot 3^{n}\cdot 9=\\ \\=(4\cdot 3)^{n}\cdot 2 +(4\cdot 3)^{n}\cdot 9=\\ \\ =12^n\cdot 2 +12^n \cdot 9=\\ \\ =12^n(2+9)=\\ \\ =12^n \cdot 11~divizibil~cu~12,~pentru~n~\in~N^*[/tex]
(2^2n+1 × 3^n + 4^n × 3^n + 2) : 12 =
(2^2n × 2 × 3^n + 4^n × 3^n × 3^2) : 12 =
(4^n × 3^n × 2 + 12^n × 9) : 12 =
(12^n × 2 + 12^n × 9) : 12 =
12^n × (2 + 9) : 12 =
12^n × 11 : 12 =
12^(n-1) × 11
__________
(2^2n × 2 × 3^n + 4^n × 3^n × 3^2) : 12 =
(4^n × 3^n × 2 + 12^n × 9) : 12 =
(12^n × 2 + 12^n × 9) : 12 =
12^n × (2 + 9) : 12 =
12^n × 11 : 12 =
12^(n-1) × 11
__________